The Impact of Frailty on 30-day Post-Elective Surgery Complications in Elderly Patients: a Prospective Cohort Study - Noto Dwimartutie; Popy Yusnidar; Susilo Chandra; Kuntjoro Harimurti (Acta Medica Indonesiana)
Background: late-life surgery poses a greater risk for complications and a higher mortality rate. Frailty has been noted to predict adverse outcomes after surgery in elderly patients. We aimed to investigate the impact of frailty on 30-day post-elective surgery complications in elderly patients. Methods: this prospective cohort study was conducted based on data collected from patients undergoing elective surgery in Cipto Mangunkusumo Hospital, Indonesia. Frailty was assessed using the Frailty Index 40 items, and 30-day post-surgery complications were assessed using Clavien-Dindo classification. Multivariate logistic regression analysis was performed to determined adjusted relative risk (RR) of the development of 30-day post-surgery complications. Results: a total of 180 subjects were enrolled in the study, with average age of 67.1 (SD 6.06) years old. More than half of the subjects fell into pre-frail category (55.6%), followed by frail (26.7%) and fit (17.7%) respectively. About 21.1% experienced complications within 30 days post-surgery. Frail subjects (41.7%) showed higher incidence of complications compared to the pre-frail (15%) and fit (9.4%) group. Multivariate analysis revealed that adjusted RR in the frail group accounted for 4.58 (95% CI 1.8-8.12), considering the surgical severity as a confounding factor. No significant difference in the incidence of complications was observed between the pre-frail and fit groups, despite the pre-frail group having a higher complication rate. Conclusion:being frail increases the risk of 30-day post-elective surgery complications in elderly patients.